Synthesis of Pyrrole by 1,5,3,7-Diazadiphosphocine-1,5-Dicarboxylic Acid as Acid Catalyst - Lee, E.J.; Lee, Y.G.; Jung, D.I.; Hahn, J.T. (Asian Journal of Chemistry, 2015)
As a part of research program related to the synthetic study of pharmacologically interesting compounds and good chelating agent for transition metal ion, we here report the synthesis of an unusual medium-sized ring heterocyclic ligand with mixed carboxylic-amino-phosphonic donating group. We have synthesized 3,7-dihydroxy-3,7-dioxoperhydro-1,5,3,7-diazadiphosphocine-1,5-diacetic acid (1a), 2-[5-(1,2-dicarboxyethyl-3,7-dihydroxy-3,7-dioxo-3[1,5,3,7]diazadiphosphocan-1-yl)-succinic acid (1b) and 3,7-dihydroxy-3,7-diox-operhydro-1,3,5,7-diazadiphosphocine-1,5-di-(2-glutaric acid) (1c). In order to analyze reactivity of synthesized dicarboxylic acids 1a-c as acid catalysts, we tried reactions of pyrrole formation according to acid variation. We know that the catalytic ability of synthesized dicarboxylic acids (1a-c) are very good at pyrrole formation reaction.